2020
DOI: 10.1163/25900323-12340004
|View full text |Cite
|
Sign up to set email alerts
|

The Semiotics of the Medical Face Mask: East and West

Abstract: After a concise survey of the state of the art on the semiotics of the mask and on studies in humanities and social sciences about medical face masks, the essay provides anecdotic evidence about differences in the semiotics of medical face masks in Europe and in the ‘Far East’, especially Japan, China, and Korea; it proposes a semiotic grid for decoding the phenomenology and meaning of the medical face mask; it concludes with some general observations on the change of the meaning of the face during the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Our analytical method draws on the basic principles of social semiotics, which focus on the elements of signification, connotative/cultural meanings and historical contexts (see Leone, 2020; Machin, 2007; Van Leeuwen, 2008). Social semiotics is not only concerned with text-level analysis, but also the understanding of how communicative practices are implicated in broader social processes.…”
Section: Data and Analytical Methodsmentioning
confidence: 99%
“…Our analytical method draws on the basic principles of social semiotics, which focus on the elements of signification, connotative/cultural meanings and historical contexts (see Leone, 2020; Machin, 2007; Van Leeuwen, 2008). Social semiotics is not only concerned with text-level analysis, but also the understanding of how communicative practices are implicated in broader social processes.…”
Section: Data and Analytical Methodsmentioning
confidence: 99%
“…Here the discipline of semiotics can be helpful. Long before the arrival of COVID-19 humans wore masks, which in turn carried different symbolic meanings [ 16 ]. Masks have historically been associated with power relations [ 17 ], ritual possession [ 18 ], the formation of secret societies [ 19 , p. 26] and situations of social reversal such as carnival [ 6 , pp.…”
Section: Masks Anti-masking and Semioticsmentioning
confidence: 99%
“…2 The messages conveyed by the COVID-19 surgical mask, in turn, reflect this diversity. For instance, a COVID mask could send the message “stay away” [ 15 , p. 255] or be a sign of what Leone refers to as the “traumatic medicalization” of the face [ 16 , p. 56]. Alternatively, the mask could simply convey one’s status as sick or contagious, which—as Leone points out—helps explain our aversion to masks [ 16 , p. 57].…”
Section: Masks Anti-masking and Semioticsmentioning
confidence: 99%
“…19 Th e text by Eco is the reprint of his Preface to the book Il Lavater portatile (con i disegni di Franco Testa), an anastatic edition, issued by the publisher Moizzi in Milan, of Johann Kaspar Lavater's physiognomic treatise from 1788. 20 Reviews of the semiotic approaches to the mask may be found in Proschan 1983, Leone 2020, Gramigna 2021 as regards the physical person who would be wearing it 21 . My proposal is to maintain the semiotic primacy of the mask over the face, to broaden the category of mask (not merely a physical object but rather a semiotic strategy) and not to reduce the mask to only one among its possible valorizations and uses.…”
Section: Face and Liementioning
confidence: 99%